Study on improving muscle mass and endurance in adults - Scheuleac Adelina; Vizitiu Lakhdari Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
Improving muscle mass is essential for maintaining health and functional capacity in adults. Strength and endurance training are recognized methods for improving these aspects, having significant benefits on general health and quality of life. The purpose of this study is to evaluate the effects of a structured physical training program on muscle mass and physical endurance in adult women aged between 48 and 51 years, who have not previously practiced physical training. Hypothesis of the paper: it is assumed that a structured physical training program will lead to a significant improvement in muscle mass and physical endurance in adult women. Objectives of the work: 1. To investigate the effects of different types of training on muscle mass and physical endurance in adults, by evaluating changes in physical parameters such as weight, cardiovascular performance measured by the Ruffier test (resting pulse, pulse in effort and recovery pulse), and muscle strength measured by Prone trunk lifts, Supine trunk lifts și Squats 2. To investigate the impact of the experimental training program on the general health of the participants before and after. The results indicate that the combined training program led to a significant increase in muscle mass and physical endurance in adults.